2021
DOI: 10.1093/cercor/bhaa404
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Interpersonal Space Permeability and Flexibility in Autism Spectrum Disorder

Abstract: Previous research indicates that the size of interpersonal space at which the other is perceived as intrusive (permeability) and the ability to adapt interpersonal distance based on contextual factors (flexibility) are altered in Autism Spectrum Disorder (ASD). However, the neurophysiological basis of these alterations remains poorly understood. To fill this gap, we used fMRI and assessed interpersonal space preferences of individuals with ASD before and after engaging in cooperative and non-cooperative social… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…As shown in Table 2, among the 12 IPD task reviews reported by the functional magnetic resonance imaging study, 11 reported changes in brain activities in the parietal lobe region of the subjects [41,42,[44][45][46][47][48][50][51][52]54]. The increased brain activity was found in the dorsal intraparietal sulcus [41,42], inferior and superior parietal cortices [44,54], inferior and superior parietal lobules [47], these functional brain activations were observed in the computerized IPD tasks, during which subjects passively watched the stimuli approaching contrast stimuli withdrawal.…”
Section: Neural Activity Of the Fmri Findingsmentioning
confidence: 91%
See 4 more Smart Citations
“…As shown in Table 2, among the 12 IPD task reviews reported by the functional magnetic resonance imaging study, 11 reported changes in brain activities in the parietal lobe region of the subjects [41,42,[44][45][46][47][48][50][51][52]54]. The increased brain activity was found in the dorsal intraparietal sulcus [41,42], inferior and superior parietal cortices [44,54], inferior and superior parietal lobules [47], these functional brain activations were observed in the computerized IPD tasks, during which subjects passively watched the stimuli approaching contrast stimuli withdrawal.…”
Section: Neural Activity Of the Fmri Findingsmentioning
confidence: 91%
“…Besides, the brain activities of a comfortable distance judgment were observed according to the CID task by EEG technique, where the subject imagines that he was the figure in the center of a circle and approached by other figures (strangers/friends) starting from the edge of the circle, and then presses the stop button at the distance where the subject feels the most comfortable. And other 3 types of the IPD-tasks evaluated the space between persons by indirect task score conversion, included the interpersonal space task [51], judgment task [56], and the choice task of social and non-social stimuli [49]. Overall, it is obvious that the results of the neural-IPD cognition were from a passive IPD pattern, while the processes of the IPD including active participation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations